(untitled) - LoCascio, Ted. (Indianapolis, 2005)
With its intuitive interface and seamless integration with other Adobe software, InDesign is rapidly gaining ground on QuarkXPress in the page layout and desktop publishing market; The only InDesign book that shows designers step by step how to produce amazing effects and cool tricks that they can immediately incorporate into their own work; A stunning full-color guide that offers a highly visual, spread-based interior design; Includes cross-platform Mac and Windows coverage
Keywords: Adobe InDesign (Electronic resource),Desktop publishing,Chế bản